EFFECT OF HERBICIDES APPLICATION ON WEED DRY MASS IN MAIZE FIELD - Mustafoyeva , Ozoda (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
The article presents data on the effect of the application of Hemglyphos and Ximstop herbicides on the dry mass of weeds in a corn field under typical sierozem soil conditions of the Tashkent province. It was found that when Hemglyphos was applied in the fall at a rate of 3.0 l/ha and Ximstop, 33% s.c. herbicide at a rate of 1.5 l/ha, when applied pre- and post-planting, annual weeds were reduced by 90.6-93.3%, their bunch mass by 86.2-89.5%, perennial weeds by 88.0-91.4%, and bunch mass by 86.0-87.6%.